Analisis Bauran Pemasaran untuk Mempengaruhi Permintaan Pasar dalam Memilih TK - Bunga Dwimala; Maimunah Maimunah (Studia Manageria, 2020)
This study aims to find out how to analyze marketing mix strategies to influence market demand and describe the impact after the implementation of the marketing mix strategy on market demand. The research method used is qualitative research and field research, where researchers conduct research directly to the research location to obtain and collect data. Data collection techniques used were interviews, observation and documentation. The results of the research mix strategy used in creating products, pay great attention to the good quality of human resources, facilities and infrastructure for playgrounds, religious learning such as Dhuha Prayers, learning to do ablution ', memorizing short letters, and especially when teaching prayer and fasting Monday and Thursday, and the facilitates entrepeneurship through the entrepeneurship Day' event, then the price is given to the upper middle standard but provides the policy of paying tuition fees in installments. Furthermore, providing scholarships for students who can not afford and students who excel. Provides good services for children and parents. A strategic place for parents to choose because the school is located on the side of the road and close to housing around Jakarta. This has become a huge market demand, and students are increasing from year to year